The Impact of Oral Hygiene Maintenance on the Association Between Periodontitis and Osteoporosis: A Nationwide Population-Based Cross Sectional Study. Issue 6 (February 2016) - Huang, Yi-Fang; Chang, Chung-Ta; Liu, Shih-Ping; Muo, Chih-Hsin; Tsai, Chun-Hao; Hong, Hsiang-Hsi; Shen, Yu-Fu; Wu, Ching-Zong
Abstract : Abstract: Both periodontitis and osteoporosis have similar sign of bone resorption in nature. However, the relationship of the severity between these 2 bone-loss diseases is still uncertain. The aim of this study was to investigate the association between the severity of osteoporosis and periodontitis regarding the impact of oral hygiene maintenance. In total, 35, 127 osteoporosis patients and 50, 498 comparisons were derived from the Longitudinal Health Insurance Database of Taiwan between 2000 and 2010. The population was subdivided into groups according to the different level oral hygiene maintenance and the severity of periodontitis and osteoporosis. The association between osteoporosis and periodontitis was estimated by multinomial logistic regression and rank correlation by Kendall rank correlation test, presented by odds ratio (OR), and 5% confidence intervals (CIs). After controlling the age, sex, and comorbidities, variables in the good oral hygiene maintenance population, we found that periodontitis raised 1.29-fold risk of osteoporosis (95% CI = 1.12–1.49); the risk of osteoporosis was increased with the elevated severity of periodontitis from 1.27 (95% CI = 1.08–1.48) to 1.38 (95% CI = 1.01–1.89). There is a positive correlation between the severity of periodontitis and osteoporosis occurrence in this population (OR = 1.27–1.46; Kendall rank correlation test P = 0.0003). In the poor oral hygiene maintenance population, periodontitis patients had 6.02-fold risk of osteoporosis than those who without periodontitis (95% CI = 4.65–7.81); the risk of osteoporosis was increased with periodontitis severity from 5.96 (95% CI = 4.48–7.92) to 6.37 (95% CI = 3.36–12.1). This result indicated the periodontitis and osteoporosis are conjunctive. The sudden periodontal breakdown of those who with good oral hygiene maintenance might be an indicator for the risk of osteoporosis; if those who were diagnosed as osteoporosis must pay more attention to their periodontal health. Good oral hygiene maintenance might be a crucial factor for preventing the deterioration of osteoporosis progressing; the oral hygiene maintenance plays a significant influence on the association between periodontitis and osteoporosis.